Serine Protease Inhibitor Kazal Type 1 (SPINK1) c.194+2T > C Mutation May Predict Long-term Outcome of Endoscopic Treatments in Idiopathic Chronic Pancreatitis. Issue 47 (November 2015) - Sun, Chang; Liu, Mu-Yun; Liu, Xiao-Gang; Hu, Liang-Hao; Xia, Tian; Liao, Zhuan; Li, Zhao-Shen
Abstract : Abstract: Endoscopic interventional is a commonly used treatment method for idiopathic chronic pancreatitis. Serine protease inhibitor Kazal type 1 (SPINK1) 194+2T>C mutation is most frequently observed in Chinese pancreatitis patients and influences the clinical course of idiopathic chronic pancreatitis patients. We conducted this study to determine the impacts of this mutation on the outcome of endoscopic treatments. In this study, we enrolled 423 patients. Among them, 101 idiopathic chronic pancreatitis patients without other relevant mutations had a successful endoscopic procedure and completed follow-up. Clinical characteristics including Izbicki pain score, exocrine and endocrine function, were evaluated. Genetic sequencing was conducted to detect SPINK1 194+2T>C mutations. The c.194+2T>C mutation was found in 58 (57.43%) patients. Factors relevant to pain relief are c.194+2T>C mutation ( P = 0.011), severe pain before treatment ( P = 0.005), and necessary subsequent endoscopic treatments ( P < 0.001). More patients with the intronic mutation had deteriorated endocrine function ( P = 0.001) relative to those patients without the mutation. Patients carrying the c.194+2T>C mutation were less likely to achieve pain relief through endoscopic treatments. They also have a higher risk of endocrine function deterioration. SPINK1 c.194+2T>C mutation may be applied as a pretreatment predictor in idiopathic chronic pancreatitis patients.